2022
DOI: 10.5194/egusphere-egu22-5489
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Glacial Rock Flour as soil fertility amendment increases N fixation activity in red clover and enhances soil N2O reduction.

Abstract: <p>The current climate trajectory in conjunction with agricultural intensification and the reliance on synthetic fertilisers, present further threat to the resilience of future food production through their contributions to soil degradation and consequent climatic feedback. Innovative sustainable agricultural technologies are needed to produce nutritious and equitable food products in line with the UN’s goal for Zero Hunger and sustainable development. Glacial Rock Flour (GRF) is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In 2022 a team of researchers from the University of Bristol conducted research that involved cultivation of red clover with nitrogen-fixing bacteria on a typical pH~7 silt loam that was treated with glacial rock dust and estimated its nitrogen fixation capacity as a measure of fertility in comparison with two equivalents; an untreated control group and one that was treated with synthetic fertilizer. The team reported that comparatively, rock dust treatments promote nitrogen fixation and mitigate N2O emissions [7]. Environmental valuables that multinational brewer Carlsberg illustrated a year earlier by increasing their crop yields with 30% after treating a barley field in Denmark with rock dust from Greenland's granite bedrock [8].…”
Section: The Theoretical Potential Of Hondsrug Glacial Rock Dust As S...mentioning
confidence: 99%
“…In 2022 a team of researchers from the University of Bristol conducted research that involved cultivation of red clover with nitrogen-fixing bacteria on a typical pH~7 silt loam that was treated with glacial rock dust and estimated its nitrogen fixation capacity as a measure of fertility in comparison with two equivalents; an untreated control group and one that was treated with synthetic fertilizer. The team reported that comparatively, rock dust treatments promote nitrogen fixation and mitigate N2O emissions [7]. Environmental valuables that multinational brewer Carlsberg illustrated a year earlier by increasing their crop yields with 30% after treating a barley field in Denmark with rock dust from Greenland's granite bedrock [8].…”
Section: The Theoretical Potential Of Hondsrug Glacial Rock Dust As S...mentioning
confidence: 99%